PENGHEMAT BAHAN BAKAR HCS PADA MESIN MOBIL DENGAN KATALIS LIMBAH PIPA A/C - Rubijanto Juni Pribadi (TRAKSI, 2015)
Supressing fuel consumption is an urgent effort to overcome fossilbased fuels issues that getting less over time. Some were attempt toovercome this issues by saving fuel consumption, while others tries toreplace the use of thsese fossils fuels comsumption with the alternativeones. The purpose of this research are to fabricate fuel saver by implementing Hydrocarbon Crack System (HCS) on Pertamax and then find the optimal HCS system volume, comparing the engine efficiency before and after the inplementation of HCS system. The HCS system in this research utilizing scrap pipes of Air Conditioner’s. The engine employed in this research is the engine of Toyota Kijang super 1998’s 1,500 cc. Research methodology in this research is to design and fabricate HCS system and then apllied it to the engine, and then performing fuel consumption, noise, emission, dan the engine’s temperatures. The results of this research shows reductions of fuel consumption after HCS application. The engine’s temperatures increasing but unsignificant.The highest noise results occurs at the smallest catalyst volume, nonidle engine (2,500 rpm) but not significant. Emission test shows thedegressions of CO and HC after implementation s of HCS on engine.The conclusions of this research are that fuel consumption is inverselyof total volumes of HCS catalist. The greater the HCS’s volume shallincreasing the engine’s tempetrature, lower noise and lower CO andHC on flue gas.